Peran Quadruple Helix dalam Meningkatkan Kreativitas dan Kapabilitas Inovasi (Studi Pada Industri Kreatif Sektor Fashion) - Mulyana -; Sutapa - (Conference In Business, Accounting, And Management (CBAM), 2015)
Creative industries are significantly contribution to economic development, however the  development of    creative industries  are  still  many  problems,  especially human resources, so it has an  impact on the innovation capability. This study aims to examine the effect of quadruple  helix (intellectual, government, business, civil soceity) to enhance the crativity and innovation capability, on sectors of fashion in Central Java. Sampling methods using purposive sampling and data analysis using the Partial Least Square (PLS). The research results     that intellectual, government, business and civil soceity  are  significantly  effect  on     the  creativity.  Intellectuals  and  business  are significantly effect on the innovation capability, but   government and civil soceity not significantly  effect  on  innovation  capability.  Creativity  is  significantly  effect  on innovation capability  Keywords: Quadruple helix, Creativity, Innovation Capability.